Fabrication of Microfibre-nanowire Junction Arrays of ZnO/SnO2 Composite by the Carbothermal Evaporation Method - Roghayeh Imani; Meysam Pazoki; Gerrit Boschloo; Aleš Iglic (Nanomaterials and Nanotechnology)
A cotton-like ZnO/SnO2 nanocomposite was grown by the carbothermal evaporation of a mixture of ZnO and SnO2 powders at 1100oC by the vapour-liquid- solid process, in which the Sn particles produced by the reduction of SnO2 act as the catalyst. Field-emission scanning electron microscope images suggest that the composites are made of microfibre-nanowire junction arrays. The structure is formed due to the fast growth of the ZnO microfibre and the subsequent epitaxial radial growth of the ZnO nanowires with Sn particles at the tips. The photovoltaic performance of the ZnO/SnO2 nanocomposite D35-cpdt dye . A dye-sensitized solar cell (DSSC) with a ZnO/SnO2 nanocomposite photoanode based on a cobalt electrolyte achieved a solar-to-electricity conversion efficiency of ∼0.34% with a short circuit current (JSC) of 0.66 mA/cm2, an open circuit voltage (VOC) of 870 mV, and a fill factor (FF) of 59. The results show the potential of this one dimensional structure in cobalt electrolyte- based DSSCs; the further optimization which is needed to achieve higher efficiencies is also discussed.